Evaluation of the Effectiveness of Surgical Treatment of Malignant Glaucoma in Pseudophakic Eyes through Partial PPV with Establishment of Communication between the Anterior Chamber and the Vitreous Cavity - Marek Rękas; Karolina Krix-Jachym; Tomasz Żarnowski (Journal of Ophthalmology)
Purpose. Determination of partial posterior vitrectomy (PPV) in the proposed modification for treatment of malignant glaucoma. Methods. The prospective, consecutive, single-center case series study involved patients in whom symptoms of malignant glaucoma occurred after combined cataract and glaucoma surgery or after glaucoma surgery in pseudophakic eye. When medical and laser treatment were not successful, partial PPV with establishment of communication between the anterior chamber and the vitreous cavity was performed. Efficacy measures were intraocular pressure (IOP) reduction, corrected distance visual acuity (CDVA), AND the number of antiglaucoma medications. Surgical success and occurring complications were also evaluated. Results. The study enrolled 20 eyes of 17 patients. Average IOP was reduced from 30.4 ± 14.2 (SD) mmHg to 14.6 ± 3.2 (SD) mmHg one year after surgery (P<0.00001). A statistically significant reduction of the number of antiglaucoma medications was obtained from 3.3 ± 1.1 (SD) preoperatively to 1.2 ± 1.1 (SD) at the end of follow-up. Statistically significant improvement of CDVA was observed 3, 6, and 12 months after surgery. Conclusions. Partial PPV with establishment of communication between the anterior chamber and the vitreous cavity enables effective IOP control over a 12-month observation; however, in most cases, it is necessary to use antiglaucoma medications for IOP control.